2020
DOI: 10.1089/jmf.2019.4625
|View full text |Cite|
|
Sign up to set email alerts
|

Physalis alkekengi Exhibits Antiobesity Effects in Mice with Potential of Inducing White Adipose Tissue Browning

Abstract: The aim of this study was to investigate the efficacy of an ethanol extract of Physalis alkekengi (PA) and its mechanistic pathway of action at the molecular level for its antiobesity properties. Four-week old male Institute of Cancer Research (ICR) mice were acclimatized for a week before starting the high-fat diet (HFD) for 2 weeks to induce obesity, followed by 8 more weeks of oral administration of 10 mg/kg orlistat and 300 mg/kg of PA extract, along with HFD. Body weights of the mice and feed and water in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
(21 reference statements)
0
1
0
1
Order By: Relevance
“…Preliminaries studies have reported presence of several active compounds, including secosteroids called physalins, and flavonoids [ 137 , 138 ]. Single compounds found in Physalis alkekengi should be studied separately to identify the main compound exerting in vivo antiobesity properties [ 139 ]. Persimmon ( Diospyros kaki ) fruit is native to China, and its cultivation extends to other part of East Asia, including Japan, where it is very popular, and it has high proanthocyanidin-type content [ 140 ].…”
Section: Anti-obesity Properties Of Polyphenolsmentioning
confidence: 99%
“…Preliminaries studies have reported presence of several active compounds, including secosteroids called physalins, and flavonoids [ 137 , 138 ]. Single compounds found in Physalis alkekengi should be studied separately to identify the main compound exerting in vivo antiobesity properties [ 139 ]. Persimmon ( Diospyros kaki ) fruit is native to China, and its cultivation extends to other part of East Asia, including Japan, where it is very popular, and it has high proanthocyanidin-type content [ 140 ].…”
Section: Anti-obesity Properties Of Polyphenolsmentioning
confidence: 99%
“…[43,45] Alkaloid ditemukan pada konsentrasi minimum di hampir semua tanaman. [40,41,42] Penghambatan adipogenesis sebenarnya masih perlu diteliti lebih spesifik mengenai kedua senyawa ini. [24]…”
Section: Pendahuluanunclassified